Optimal Timing for Resuming Antithrombotic Agents and Risk Factors for Delayed Bleeding after Endoscopic Resection of Colorectal Tumors - Kazuko Beppu; Taro Osada; Naoto Sakamoto; Tomoyoshi Shibuya; Kenshi Matsumoto; Akihito Nagahara; Takeshi Terai; Tatsuo Ogihara; Sumio Watanabe (Gastroenterology Research and Practice)
Aim. To examine optimal timing for resuming antithrombotic agents and risk factors for delayed bleeding after endoscopic resection of colorectal tumors. Method. Of 1,970 polyps larger than 10 mm removed by polypectomy, endoscopic mucosal resection, or endoscopic submucosal dissection, delayed bleeding, which was designated as bleeding that occurred 6 or more hours after endoscopic treatment, occurred in 52 cases (2.6%); 156 nonbleeding cases matched for age and gender were controls in this single-institution retrospective case-control study. We investigated (1) patient-factors: resuming antithrombotic agents within 5 days following endoscopic resection, hypertension, and diabetes mellitus; and (2) tumor-factors: morphology, size, location, and resection technique by conditional logistic regression. Results. By multivariate analysis resumption of anticoagulants within 5 days was a significant risk factor for delayed bleeding (OR 10.2; 95% CI = 2.7–38.3; P=0.0006). But resuming a thienopyridine within 5 days was not (OR 0.9; 95% CI = 0.1–2.6; P=0.40). Other patient- and tumor-factors were not significant. Conclusion. Resuming anticoagulants within 5 days after endoscopic treatment was associated with delayed bleeding whereas resuming thienopyridines was not.